Productivity driven growth: problems & possibilities - Abdullah, Maisom (2002)
When Malaysia embarked on an industrial development path beginning with the Pioneer Industries Ordinance (1985) followed by the Investment Incentive Act (1968), the growth of the economy was fuelled by increasing utilization of factors of production, mainly capital and labour. Dependence on this “investment-driven growth” is manifested by the heavy dependence on industries which depend strongly on foreign investments including electronics and textiles. Economists and other scholars are aware that high achieving and competitive economies such as Japan and Germany are productivity-driven rather than input-driven. Efforts to redirect the Malaysian industrial development towards a productivity-driven path were initiated in the 1980’s through measurements and analysis of both partial and total factor productivity growth (TFPG). Major factors which will determine a productivity-led growth are identified as technological progress and innovation, quality management, human resource development, and improvements in quality of capital formation and investments. Malaysia is now ready to embark on a comprehensive path of productivity-driven growth as envisaged in the productivity Master Plan (2000) and the implementation of consecutive 7th and 8th Malaysia Plans.